Chondrodysplasia Punctata in a Newborn; Rhizomelic Type: A Case Report - Naher, Begum Sharifun; Mannan, MA; Noor, Khaled; Shahidullah, Md (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v34i1.5700 Bangladesh Journal of Child Health 2010; Vol.34(1): 28-30